2011
DOI: 10.1103/physreve.83.036606
|View full text |Cite
|
Sign up to set email alerts
|

New family of solitary waves in granular dimer chains with no precompression

Abstract: In the present paper we report the existence of a new family of solitary waves in general one-dimensional dimer chains with elastic interactions between beads obeying a strongly nonlinear Hertzian force law. These dimers consist of pairs of "heavy" and "light" beads with no precompression. The solitary waves reported herein can be considered as analogous to the solitary waves in general homogeneous granular chains studied by Nesterenko, in the sense that they do not involve separations between beads, but rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
129
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(140 citation statements)
references
References 14 publications
10
129
1
Order By: Relevance
“…[48][49][50][51][52][53] In general, the magnitude of n depends upon the contact geometry between the beads and typically varies between n = 5/2 and 3. 28,47,54 If there is great enough prestress, the bead radius will be R ′ = R − δ 0 2 , δ 0 is the initial overlap deformation between two beads.…”
Section: Modelmentioning
confidence: 99%
“…[48][49][50][51][52][53] In general, the magnitude of n depends upon the contact geometry between the beads and typically varies between n = 5/2 and 3. 28,47,54 If there is great enough prestress, the bead radius will be R ′ = R − δ 0 2 , δ 0 is the initial overlap deformation between two beads.…”
Section: Modelmentioning
confidence: 99%
“…Geometry and/or material anisotropy between particles composing the systems allows for the observation of interesting dynamic phenomena deriving from the interplay of discreteness and nonlinearity of the problem (i.e. anomalous reflections, breathers, energy trapping and impulse fragmentation) [11,12,19,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. These findings open up a large parameter space for new materials design with unique properties sharply departing from classical engineering systems.…”
Section: Introductionmentioning
confidence: 99%
“…when  approaches 0, the lattice becomes a so-called "auxiliary system" 32 . The radii of GNS in homogeneous lattice and heavy GNS in diatomic lattice are both R0 = 2.5 nm.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that n is a decreasing function of , but with a slowing-down rate, suggesting that for 15 nanoparticles, contact nonlinearity can be increased by creating mass difference. It is shown in literature that nonlinear resonances in uncompressed diatomic granular crystals result in a significant wave attenuation, which, from a practical point of view, could be employed as passive shock attenuators 32 . A transmission rate  is defined as P max,last imp / vv   to evaluate the attenuation performance of the diatomic GNS granular crystals, where P max,last v is the maximum particle velocity of the last GNS, Different from macroscale diatomic lattices governed by Hertzian contact, governing Eq.…”
Section: Diatomic Gns Granular Crystalsmentioning
confidence: 99%
See 1 more Smart Citation